Gerakan Dakwah Filantropi Dalam Lembaga ZISWAF :Tinjauan Program Dompet Dhuafa Dalam Mengatasi Kemiskinan - Kholifah, Nur; Faisal Bakti , Andi; Napsiyah , Siti (Program Studi Manajemen Dakwah - Fakultas Dakwah dan Ilmu Komunikasi - UIN Syarif Hidayatullah Jakarta, 2025)
Da'wah plays a crucial role for the Muslim community. It is not limited to delivering religious sermons, but can also take the form of efforts to liberate people from poverty through philanthropic da'wah, which functions to build the economic growth of the ummah across various sectors by utilizing Zakat, Infaq, Sadaqah, and Waqf (ZISWAF). The purpose of this study is to explain how the philanthropic da'wah movement is realized through Dompet Dhuafa's programs, particularly in its efforts to reach and empower impoverished communities. The research method used is qualitative with a library research approach. The data sources for this study are secondary sources, including information from the Dompet Dhuafa website, internal documents such as annual reports, as well as relevant books and academic journals. The findings reveal that Dompet Dhuafa has undergone a significant transformation into a professional, empowerment-based institution. Its programs go beyond direct aid and are oriented toward fostering community self-reliance. Thus, the philanthropic da'wah movement through ZISWAF institutions proves to be an effective strategy for poverty alleviation and the realization of social justice. Keywords: Philanthropic Da'wah; ZISWAF; Dompet Dhuafa; and Poverty